IDDF2019-ABS-0192 Compliance to probiotic therapy in irritable bowel syndrome in clinical practice: a real-life study. (7th June 2019) - Laterza, Lucrezia; Napoli, Marco; Scaldaferri, Franco; Petito, Valentina; Colombo, Stefano; Gasbarrini, Antonio
Abstract : Background: Probiotics have been evaluated in multiple clinical trials on irritable bowel syndrome (IBS) showing efficacy on different IBS-related symptoms. Among them, the multistrain probiotic VSL#3 has been the object in clinical trials evaluating its administration for 4 to 8 weeks. However, in real-life long term compliance could be low. Furthermore, in many country probiotics are fully paid by patients and the cost of therapy could further limit the compliance to probiotic therapy. Methods: This is a single-center, observational, prospective study to evaluate the compliance to prescription of probiotic therapy in real life and to identify factors able to influence adherence to therapy. Patients diagnosed with IBS (either diarrhea, constipation or mix-type) according to Rome IV criteria and receiving a clinical prescription of VSL#3 for their IBS symptoms were evaluated for eligibility. Patients providing informed consent, were evaluated after 2 months to assess compliance and eventual reasons for discontinuation. Results: Thirty-four patients, twenty-four women (70.6%) and ten male (29.4%), have been enrolled. Thirteen of them (38.2%) were IBS-D patients, fourteen (41.2%) were IBS-C patients and six (17.6%) were IBS-mix patients. The average age was 40.5 years. Twenty-seven of thirty-four patient received a 4 weeks prescription of VSL#3, whereas five patients received a 2 weeks prescription and two patients an 8 week prescription. All the 34 patients completed the 2 month-follow up for outcomes evaluation. Twenty-one patients (61.8%) assumed the therapy as prescribed. Among the thirteen patients (38.2%) who referred to reduced compliance, nine (64.3%) of them assumed at least 50% of probiotic doses prescribed. The main reasons for discontinuation were low palatability (n=3), bloating (n=3) and price of the product (n=6). One patient enrolled forgot to take the medication. Among AE, bloating has been reported in six (17.6%) cases. No SAE was reported. Conclusions: According to our results, about 60% (61.8) of patients assumed all the prescribed probiotic therapy in a real life setting, despite a good safety profile. The main reasons for lack of compliance were palatability, bloating and price of the product.